ABO blood type and risk of porcine bioprosthetic aortic valve degeneration: SWEDEHEART observational cohort study. Issue 5 (5th May 2019) - Persson, Michael; Edgren, Gustaf; Dalén, Magnus; Glaser, Natalie; Olsson, Martin L; Franco-Cereceda, Anders; Holzmann, Martin J; Sartipy, Ulrik
Abstract : Objective: Blood type A antigen on porcine aortic bioprostheses might initiate an immune reaction leading to an increased frequency of structural valve deterioration in patients with blood type B or O. The aim was to analyse the association between ABO blood type and porcine bioprosthetic aortic valve degeneration. Design: Observational nationwide cohort study. Setting: Swedish population-based study. Participants: Adult patients (n=3417) who underwent surgical aortic valve replacement and received porcine bioprosthetic aortic valves between 1995 and 2012 from the Swedish Web system for Enhancement and Development of Evidence-based care in Heart disease Evaluated According to Recommended Therapies register. The study database was enriched with information from other national registers. Exposure: The patients were categorised into type A/AB and type B/O blood groups. Primary and secondary outcome measures: Primary outcome measure was aortic valve reoperation, and secondary outcomes were heart failure and all-cause mortality. We report risk estimates that account for the competing risk of death. Results: In total, 3417 patients were identified: 1724 (50.5%) with blood type A/AB and 1693 (49.5%) with blood type B/O. Both groups had similar baseline characteristics. The cumulative incidence of aortic valve reoperation was 3.4% (95% CI 2.5% to 4.4%) and 3.6% (95% CI 2.6% to 4.6%) in the type B/O and the A/AB group, respectively, at 15 years of follow-up (absolute risk difference: −0.2% (95% CI −1.5% to 1.2%)). There was no significantly increased risk for aortic valve reoperation in patients with blood type B/O compared with type A/AB (HR 0.95, 95% CI 0.62 to 1.45). There was no significant difference in absolute or relative risk of heart failure or death between the groups. Conclusions: We found no significant association between patient blood type and clinical manifestations of structural valve deterioration following porcine aortic valve replacement. Our findings suggest that it is safe to use porcine bioprosthetic valves without consideration of ABO blood type in the recipient. Trial registration number: NCT02276950